A Semiotic Analysis of Youth Representation in Silverqueen Television Advertisements - Novia Mayasari (Passage, 2015)
This qualitative study aims to analyze the youth representation in five versions of SilverQueen television advertisements and reveal the ideologies reflected in such representation. The data are five versions of SilverQueen television advertisements which are broadcasted in Indonesia from 2002 until 2012. The theories used in this study are Barthes’ orders of signification (1957) and the theory of visual elements proposed by Dyer (1996). The findings of the study show that youth is represented in five versions of SilverQueen television advertisements (2002-2012) through similar ways. Youth is represented in SilverQueen television advertisements through three visual elements (actor, setting, and property): (1) the attractive young people as actors and actresses of the advertisements who are estimated to be about 18-25 years old. They wear casual clothes which represent informality and some accessories which make their appearances look more attractive; (2) the choices of setting which mostly take place outdoors represent the youth’s interest for spending their free time outdoors and enjoying nature; and (3) the choices of property reflect that young people love to relax, hang out with their friends, and have interest for exploration and visiting places. In terms of ideologies, this study found two ideologies behind such representation, namely freedom and hedonism. Keywords: youth, representation, television advertisement, ideology